Manajemen Pemasaran Pendidikan di Pondok Pesantren Nurul Islam 1 Jember - Zawawi, M. Ilmil (MANAGIERE: Journal of Islamic Educational Management, 2024)
Competition in the marketing of educational institutions is increasingly inevitable, because it requires institutions to always innovate to meet needs, provide satisfaction, have excellence, and maintain their existence to service users through marketing components, namely segmentation, targeting and positioning. Meanwhile, Islamic boarding schools have a role and responsibility for the morals of the nation's generation of children, education is carried out through formal and non-formal channels. The research objectives are 1) to describe the segmentation of educational marketing management at the Nurul Islam 1 Jember Islamic boarding school, 2) to determine the targeting of marketing management at the Nurul Islam 1 Jember Islamic boarding school, 3) to determine the positioning of educational marketing management at the Nurul Islam 1 Jember Islamic boarding school. This research is a qualitative descriptive research with a case study type. Data collection techniques used passive participant observation, semi-structured interviews, and documentation. Data validity uses triangulation and member checks. Research results 1) Segmentation in education marketing through regional mapping, specialization tests and STIFIn as well as superior programs, 2) Targeting from all groups by offering scholarship programs and price variants, clear scientific knowledge and complete formal education, 3) Positioning is known as the ASWAJA direction, a multitude of academic and non-academic achievements, a guarantee of memorizing 30 Juz of the Al-Quran, and being educated to become a writer.